DEVELOPING ENGLISH LISTENING MATERIALS THROUGH SONG FOR THE ELEVENTH GRADE STUDENTS OF NETWORK COMPUTER ENGINEERING - Meida Rabia Sihite; Linda Astuti Rangkuti; Annisa Pratama (Institut Pendidikan Tapanuli Selatan, 2022)
The objective of this study is to develop appropriate listening materials through song for the eleventh grade students of Network Computer Engineering at SMK Karya Setia Pegajahan. This study was a Research and Development (R & D). The steps of this study were: conducting needs analysis, designing the syllabus and the first draft of the material, judging by expert, and writing the final draft of the materials. The results of the study indicated that (1) English is very important for future job as a technician; (2) Mastering English is crucial to pass the National Examination; (3) The students also want the teacher to explain the formulas before discussing a task and leading the students in discussing a particular text. The activities applied five steps of the scientific approach: observing, questioning, collecting, analyzing, and communicating. Based on the data analysis from the expert judgment, the mean score of all aspects of the three developed units is 3.88 which is in the range of 3.25 ≤ x̄ ≤ 4.00 and can be categorized as “Very Good”.